A review on machining performance of AISI 304 steel. (2022) - Kumar, Amresh; Sharma, Rajesh; Kumar, Santosh; Verma, Prajjawal
Abstract: Austenitic stainless steels (AISI 304) is most versatile grade in stainless steel and widely used in various industries owing to its attractive properties. It has high durability, high ductility, toughness at cryogenic temperature and excellent resistance against corrosion. In addition, this steel has excellent weldability, high resistance against fatigue and oxidation. However, owing to their high work hardening, high built up edge and low heat conductivity, AISI 304 stainless steel is considered as most difficult to-cut material than other alloy steels. To overcome this, various cutting fluids are used to enhance the life of cutting tools, reduce cutting temperature, reduce friction between tool and workpiece, and to improve the machining efficiency and surface integrity. Thus, the aim of this review paper is to summarize the various investigations done by distinct researchers on machining performance of AISI-304 stainless steel. In addition, various applications and factor that affect the performance of AISI-304 stainless steel are also discussed, so that this paper could become useful for the futuristic researchers to select optimum machining parameters, coolant type and machine for improving the overallmachined surface integrity.